2016
DOI: 10.1128/aac.02651-15
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Ocular Infection Caused by Staphylococcus aureus Bacteremia

Abstract: Staphylococcus aureus bacteremia (SAB) often leads to ocular infections, including endophthalmitis and chorioretinitis. However, the incidence, risk factors, and outcomes of ocular infections complicated by SAB are largely unknown. We retrospectively analyzed the incidence and risk factors of ocular involvement in a prospective cohort of patients with SAB at a tertiary-care hospital. Ophthalmologists reviewed the fundoscopic findings and classified the ocular infections as endophthalmitis or chorioretinitis. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
2
8
0
1
Order By: Relevance
“…Endophthalmitis is especially prevalent with S. aureus IE. For instance, in a prospective cohort of patients with S. aureus bacteraemia, 10 out of 23 (43%) patients who had IE also had ocular infection 91 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Endophthalmitis is especially prevalent with S. aureus IE. For instance, in a prospective cohort of patients with S. aureus bacteraemia, 10 out of 23 (43%) patients who had IE also had ocular infection 91 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…A retrospective 10-year review identified only 28 cases with 40% of these attributable to bacteraemia from endocarditis 2. In those with Staphylococcus aureus bacteraemia and ocular involvement, infective endocarditis was found to be an independent risk factor for the development of endopthalmitis 3. The streptococcus species (as seen in this case) are the most commonly implicated bacterial pathogens, reported to cause between 30% and 50% of cases 1…”
Section: Discussionmentioning
confidence: 64%
“…When SAB is associated with endophthalmitis, it is a cause for concern because it may be difficult to diagnose and challenging to manage. Four of the 15 patients with endophthalmitis associated with SAB died within 12 weeks after onset of SAB in a large single centre prospective study in South Korea 13. Subretinal abscesses have been described in association with SAB following spread from various primary sites of infection such as from vertebral osteomyelitis 14.…”
Section: Introductionmentioning
confidence: 99%